(untitled) (Research, Society and Development, 2022)
The family structure and dynamics have changed over time, as has the understanding and design of this institution. It is believed that the exploration of these different structures and conceptions is important for understanding the family today. This theoretical article aims to carry out a brief historical review of the family, from prehistory to contemporaneity in Western society, especially in Brazilian society. Therefore, through bibliographical research, the contributions of the main researchers on the family in its historical, social, economic, political, anthropological and psychological path and the repercussions of this path on the contemporary family were addressed. It was concluded that the family cannot be explained from a single and universal model; therefore, it is necessary to consider the complexity, polymorphism and plurality in their configurations in post-modernity.